Guadalupe Ortiz de Landázuri en México. El alcance espiritual de una sensibilidad lingüística / Guadalupe Ortiz de Landázuri in Mexico. The spiritual significance of a linguistic sensibility - Rafael Jiménez Cataño (Studia et Documenta)
This brief study attempts to show how Guadalupe Ortiz de Landázuri understood well the Mexican colloquialism ni modo, which is not often used correctly by Spaniards, and used it in a way that manifests a very central realism of the charisma of Opus Dei. The conditions that favored this perception are seen: her willingness to assume aspects of the life of the country that welcomed her, and the fact that this idiom gave effective expression to her way of facing the challenges of life. The tools offered by pragmatic linguistics (in particular the theory of politeness) are used to analyze Ortiz de Landázuri’s situation in the Mexican socio-cultural milieu, with examples of the literary use of the same expression. Some formulations of that charisma that we see so well expressed in Guadalupe’s use of the analyzed colloquialism are also pointed out.